Presence of risk factors for thyroid cancer does not improve the performance of ultrasound screening for thyroid nodules in patients with obesity. Issue 7 (14th April 2021) - Gimenez‐Perez, Gabriel; Recasens, Assumpta; Chicharro, Sandra; Simo, Olga; Murillo, Jesus; Castells, Ignasi
Abstract: Purpose: It has been suggested, on a theoretical basis, that ultrasound screening of thyroid nodules in obese patients with additional risk factors (family history, chronic autoimmune thyroiditis or high thyrotropin) might be cost‐effective for the early detection and treatment of thyroid cancer. The present study evaluates if this approach can be validated in a real clinical setting. Methods: Patients with obesity who attended hospital‐based clinics were evaluated for risk factors of thyroid cancer and ultrasound screened for thyroid nodularity. Detected nodules were evaluated according to current guidelines. Results: A total of 429 patients were evaluated (70.2% women, mean age 49.1 ± 11.0, mean body mass index 42.6 ± 5.8 kg/m 2 ). Risk factors were present in 129 (30.1%) patients. Thyroid nodules with indication for fine‐needle aspiration biopsy were detected in 69 (16.1%). We did not find differences in the risk of harbouring thyroid nodules according to the presence of risk factors (no risk factors 16.6%, risk factors 14.1%, P  = .64). No single risk factor conferred an increased risk for thyroid nodules During the screening procedure, four cases of thyroid cancer were detected, none of them with the evaluated risk factors. Conclusion: The presence of known risk factors for thyroid cancer does not improve the performance of a US screening strategy aimed at the detection of thyroid nodules in obese patients. According to current guidelines, screening for thyroid nodules in obese patients is not recommended regardless of the presence of thyroid cancer risk factors.